2006
DOI: 10.1111/j.1747-4949.2005.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Symptomatic Intracranial Atherosclerosis

Abstract: Intracranial atherosclerosis is a common cause of stroke, accounting for about 50% of ischaemic stroke in Asia and 8% in North America. Many prospective studies have confirmed that intracranial stenosis is an independent predictor for poor outcomes such as recurrent vascular event and death, despite the use of antiplatelet agents. The annual event rate is about 15% per year. The dismal outcome prompts the study of more aggressive treatment strategies, including warfarin and endovascular intervention. We have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…In Chinese patients and other Asian groups, there is a greater incidence of small vessel disease and intracranial large vessel stenosis. 23 This has also led to the speculation that there may be differing dosing requirements in Asia.…”
Section: Discussionmentioning
confidence: 98%
“…In Chinese patients and other Asian groups, there is a greater incidence of small vessel disease and intracranial large vessel stenosis. 23 This has also led to the speculation that there may be differing dosing requirements in Asia.…”
Section: Discussionmentioning
confidence: 98%
“…41 The medical management of ICAD has evolved dramatically in the past decade. 42 In this study, we extended the use of aspirin and clopidogrel to 4 weeks based on our initial experience of dual antiplatelets in reducing the frequency of ipsilateral distal microemboli. To test the true effect of dual antiplatelets, we excluded aspirin-failure patients to minimize the concern of aspirin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Angioplasty has been reported in many retrospective studies to have reasonable success rates with periprocedural complication rates reported of 4–40% 12 106. Initial series of angioplasty alone had higher complication rates but the technique of submaximal angioplasty, where the angioplasty balloon is undersized relative to the target vessel, appears to have lowered complications.…”
Section: Summary Of Evidence Regarding Treatmentmentioning
confidence: 99%